2002
DOI: 10.1039/b200989g
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic transition in proteins may have a simple explanation

Abstract: The transition that has been observed in the dynamics of hydrated proteins at low temperatures (180-230 K) is normally interpreted as a change from vibrational, harmonic motion at low temperatures to anharmonic motions as the temperature is raised. It is taken to be an intrinsic property of proteins and has been associated with the onset of protein functions. Examination of the dynamic behaviour of proteins in solution within a defined timescale window suggests that certain observations can be explained withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
(79 reference statements)
4
20
0
Order By: Relevance
“…This observation is also in accord with recent molecular dynamics simulation results which indicate that deviation from harmonic dynamics in a small protein in vacuo is apparent at temperatures as low as 120 K [36,37], and also with experimental results demonstrating the appearence of a transition at similarly-low temperatures in a membrane protein [38]. In experiments on hydrated powders or enzyme solutions the change in slope at 200-250 K was found to be dependent on the energy resolution [39,40], indicating that the apparent position of the dynamical transition depends on the timescale explored [31,30] consistent with molecular dynamics simulations that indicate that the transition does not involve an abrupt change from harmonic to anharmonic dynamics [41]. At a low enough temperature the quasielastic scattering should no longer be visible, as the associated relaxation time will have moved to slower timescales than can be detected on the instrument.…”
Section: Discussionsupporting
confidence: 90%
“…This observation is also in accord with recent molecular dynamics simulation results which indicate that deviation from harmonic dynamics in a small protein in vacuo is apparent at temperatures as low as 120 K [36,37], and also with experimental results demonstrating the appearence of a transition at similarly-low temperatures in a membrane protein [38]. In experiments on hydrated powders or enzyme solutions the change in slope at 200-250 K was found to be dependent on the energy resolution [39,40], indicating that the apparent position of the dynamical transition depends on the timescale explored [31,30] consistent with molecular dynamics simulations that indicate that the transition does not involve an abrupt change from harmonic to anharmonic dynamics [41]. At a low enough temperature the quasielastic scattering should no longer be visible, as the associated relaxation time will have moved to slower timescales than can be detected on the instrument.…”
Section: Discussionsupporting
confidence: 90%
“…We expect that dehydrated RNAs have a different sea structure, the dynamics of which remain superpositions of harmonic motions. This view is consistent with a model that collectively accounts for all evidence to date simply by assuming that motions of biomolecules in solution slow down continuously with temperature (68). In this model, the observed dynamical transition may be Biophysical Journal 108(12) 2876-2885 no more than the appearance of motions within the observational timescale window of the experimental apparatus used.…”
Section: Discussionsupporting
confidence: 68%
“…However, a recent conductivity study of the lysozyme-glycerol system demonstrated that the ion transport dynamics are coupled with the structural relaxation of glycerol, i.e., no anomalies were found at and near T D [17]. Rather, on the basis of neutron scattering experiments, the existence of a dynamic protein transition has been questioned [18], thereby confirming reports that T D can depend on the experimental time window [19,20].…”
Section: Introductionmentioning
confidence: 82%